2007
DOI: 10.1017/s1748499500000233
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Claim Duration of Income Protection Insurance Policyholders using Parametric Mixture Models

Abstract: This paper considers the modelling of claim durations for existing claimants under income protection insurance policies. A claim is considered to be terminated when the claimant returns to work. Data used in the analysis were provided by the Life and Risk Committee of the Institute of Actuaries of Australia. Initial analysis of the data suggests the presence of a long-run probability, of the order of 7%, that a claimant will never return to work. This phenomenon suggests the use of mixed parametric regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…However, this power comes at a price ö the basic assumption, that the effect of each covariate is multiplicative, is very strong. It is interesting to note that in relation to the modelling of claim termination rates for Australian IP data, Pitt (2007) reported that there were clear violations of the assumption of proportional hazards for some of the key rating factors. However, Pitt did not allow for the possibility of duration-varying effects, i.e.…”
Section: Overviewmentioning
confidence: 99%
“…However, this power comes at a price ö the basic assumption, that the effect of each covariate is multiplicative, is very strong. It is interesting to note that in relation to the modelling of claim termination rates for Australian IP data, Pitt (2007) reported that there were clear violations of the assumption of proportional hazards for some of the key rating factors. However, Pitt did not allow for the possibility of duration-varying effects, i.e.…”
Section: Overviewmentioning
confidence: 99%
“…In order to make the interpretation of results simpler, we restrict ourselves in this paper to the consideration of the effect of age, occupation class (C or D vs A or B). (See Pitt (2006a) for a description of occupation classes) and deferred period (greater than or equal to 28 days or less than 28 days).…”
Section: â Regression Quantiles and Claim Termination Ratesmentioning
confidence: 99%
“…A censored regression quantile model was fitted using the entire dataset of claim durations described in Pitt (2006a). The R (2005) command used to fit the model is:…”
Section: â Regression Quantiles and Claim Termination Ratesmentioning
confidence: 99%
See 2 more Smart Citations